Tolvaptan for Children and Adolescents with Autosomal Dominant Polycystic Kidney Disease: Randomized Controlled Trial. Issue 1 (January 2023) - Mekahli, Djalila; Guay-Woodford, Lisa M.; Cadnapaphornchai, Melissa A.; Greenbaum, Larry A.; Litwin, Mieczyslaw; Seeman, Tomas; Dandurand, Ann; Shi, Lily; Sikes, Kimberly; Shoaf, Susan E.; Schaefer, Franz
Visual Abstract: Abstract : Background: Tolvaptan slows expansion of kidney volume and kidney function decline in adults with autosomal dominant polycystic kidney disease (ADPKD). Progression during childhood could be treated before irreversible kidney damage occurs, but trial data are lacking. We evaluated the safety and efficacy of tolvaptan in children/adolescents with ADPKD. Methods: This was the 1-year, randomized, double-blind, portion of a phase 3b, two-part trial being conducted at 20 academic pediatric nephrology centers. Key eligibility criteria were ADPKD and eGFR ≥60 ml/min per 1.73 m 2 . Participants aged 12–17 years were the target group (group 1, enrollment goal n ≥60); participants aged 4–11 years could additionally enroll (group 2, anticipated enrollment approximately 40). Treatments were tolvaptan or placebo titrated by body weight and tolerability. Coprimary end points, change from baseline in spot urine osmolality and specific gravity at week 1, assessed inhibition of antidiuretic hormone activity. The key secondary end point was change in height-adjusted total kidney volume (htTKV) to month 12 in group 1. Additional end points were safety/tolerability and quality of life. Statistical comparisons were exploratory and post hoc . Results: Among the 91 randomized (group 1, n =66; group 2, n =25), least squares (LS) mean reduction (±SEM) in spot urine osmolality at week 1 was greater with tolvaptan (−390 [28] mOsm/kg) than placebo (−90 [29] mOsm/kg; P <0.001), as was LS mean reduction in specific gravity (−0.009 [0.001] versus −0.002 [0.001]; P <0.001). In group 1, the 12-month htTKV increase was 2.6% with tolvaptan and 5.8% with placebo ( P >0.05). For tolvaptan and placebo, respectively, 65% and 16% of subjects experienced aquaretic adverse events, and 2% and 0% experienced hypernatremia. There were no elevated transaminases or drug-induced liver injuries. Four participants discontinued tolvaptan, and three discontinued placebo. Quality-of-life assessments remained stable. Conclusions: Tolvaptan exhibited pharmacodynamic activity in pediatric ADPKD. Aquaretic effects were manageable, with few discontinuations. Clinical Trial registry name and registration number: Safety, Pharmacokinetics, Tolerability and Efficacy of Tolvaptan in Children and Adolescents With ADPKD (Autosomal Dominant Polycystic Kidney Disease) NCT02964273.